1861 Terr. of Nev. Stat. 61, ch. 28, §§ 35-36 - (:unkn) unknown (General Publisher, 1861)
Provided that the killing of another in a duel with a rifle, shotgun, pistol, Bowie knife, dirk, small-sword, back-sword, or other “dangerous weapon” in the killing of another in a duel is to be deemed murder.
--
Keywords: DUELING